54.8k views
1 vote
What equation do you get when you solve p = 2l + 2w for w

User Nick Fury
by
5.0k points

1 Answer

2 votes

Answer: When you solve for w the equation is
w= (p-2l)/(2)

Explanation:

p = 2L + 2w subtract 2L from both sides

p -2L = 2L -2L + 2w 2L-2L = 0 om the right; they cancel

p - 2L = 2w now get w alone

(p - 2L)/2 = 2w/2 divide both sides by 2 2w/2 = w 2/2=1 it "cancels"


(p +2L)/(2) = w rewrite Reverse sides to put w alone on the left side


w= (p-2l)/(2)

User Aidrivenpost
by
5.4k points